SOSIALISASI PEMBUATAN BIO-PESTISIDA DARI LIMBAH PUNTUNG ROKOK - Putra, Rifki Mahesa; Maryani, Eny; Afro , Maulina Nafsiatil; Karmila; Juliana, Darma; Putra, Masaradi; Rukmana, Lisma Hardianti; Aini, Echa; Ramadhan, Syarifurrizal; Jannah, Nadiatul; Prastiyanto, Wahyu; Sakti, Dwi Putra Buana (Universitas Mataram, 2024)
Pesticides are substances used to kill or control various pests. Most pesticides are synthetic chemicals with classification based on active ingredients such as Amamketin benzoate. The purpose of making bio-pesticides by utilizing the remaining cigarette butt waste from Pringgasela Village and creating bio-pesticides that can help farmers in Pringgasela village to eradicate pests that attack plants and are more environmentally friendly. Bio-pesticide development can be done by utilizing waste waste that has certain active ingredients in eradicating pests, one of which is cigarette butts. Making bio-pesticides using cigarette butts then put in a bottle filled with water and mixed with detergent, then fermented for 7 days. This bio-pesticide is easy to make by yourself, especially by farmers as consumers, and is also relatively safe for the environment. Cigarette butts have the same content as dried tobacco leaves, such as nicotine, phenol, and eugenol. The target pests of the biopesticide made from cigarette butts are small pests such as aphids, trips, aphis armyworms and mealybugs and even the intensity of mealybug attacks. Based on the socialization carried out, it went smoothly and successfully in making bio-pesticides because it was supported by the qualified knowledge of the community, in Pringgasela village for the education taken by the community.